THE EFFICACY OF DECENTRALISATION IN PROMOTING GOOD GOVERNANCE: A CASE STUDY OF THE KPANDAI DISTRICT OF THE NORTHERN REGION OF GHANA - Sulemana Achanso, Adams (Advances in Social Sciences Research Journal, 2020)
A country’s democratic process is considered to be on a sound footing when its citizens are able to meet their basic needs, such as access to quality health care, housing, infrastructure, education, job security and what have you. This is what gives credence to decentralisation as a mechanism for bringing governance to the door steps of the citizenry. Ghana introduced its current decentralised governance system since 1992 to devolve central government’s authority to the district level in order to bring governance close to the citizenry. This study assessed the efficacy of Ghana’s decentralisation system as a mechanism for promoting good governance using the Kpandai District of the Northern Region of Ghana as a case study. The study benefited from both secondary and primary data collected and analysed using both the quantitative and qualitative research strategies. The study suggested that citizens’ participation in both local and national level decision making processes were low mainly due to communication barriers between the electorates and their representatives. This was a result of inadequate public education or sensitisation on citizens’ participatory processes. The study, therefore, suggested the need for awareness creation on citizens’ rights to participate in decision making processes and elected representatives to report on their activities to their constituents as a way of feedback to allow citizens to demand their rights in order to enhance their wellbeing.